Single-component lipid nanoparticles for engineering SOCS1 gene-silenced dendritic cells to boost tumor immunotherapy. (28th November 2022) - Yu, Zexuan; Wu, Mengtong; Huang, Yingshuang; Wang, Yishu; Chen, Yijun; Long, Qiulin; Lin, Ziming; Xue, Lingjing; Ju, Caoyun; Zhang, Can
Abstract : Single-component lipid nanoparticles are designed and prepared for delivery of SOCS1 siRNA to primary DCs, which can be further pulsed with Ova-antigen to fabricate a SOCS1-downregulated DC vaccine with the potential to boost antitumor immunotherapy. Abstract : Dendritic cells (DCs) that can prime antitumor responses show great potential in tumor immunotherapy, whereas the unsatisfactory effect which can be ascribed in part to the high expression of inhibitory cytokines, such as the suppressor of cytokine signaling 1 (SOCS1), restricts their application. Thus, silencing these genes in DCs is essential for DC-based therapy. However, safe and effective delivery of siRNA to DCs still faces challenges. Herein, we designed single-component lipid nanoparticles comprising a solely cationic lipid (OA2) for introducing siRNA into mouse DCs in order to inhibit the immunosuppressive gene and boost the effector responses of DC-based therapy. Compared to other multi-component lipid nanoparticles, single-component lipid nanoparticles are theoretically easy-to-control and detective, which is beneficial for future translation. We showed that the application of OA2 lipid nanoparticles significantly downregulated the expression of SOCS1 in DCs over 50%, compared with the commercial lipofectine2000. Besides, the treatment of OA2 lipid nanoparticles had no influence on the antigen capture of DCs. Thus, we fabricated a SOCS1-downregulated DC vaccine pulsed with Ova antigen and demonstrated that the antigen presentation and pro-inflammatory factor secretion ability of DCs were improved due to the SOCS1 downregulation, leading to an ameliorated immunosuppressive tumor microenvironment and finally exhibiting potent tumor prevention and suppression in B16-Ova tumor-bearing mice. Single-component lipid nanoparticles, which provide an available vector platform for siRNA delivery to primary DCs, appear to be a potent tool to engineer DCs and in turn boost DC-based tumor immunotherapy.